The Management of Superior Dislocation of the Patella with Interlocking Osteophytes—An Update on a Rare Problem - DKH Yip; JWK Wong; LK Sun; NM Wong; CW Chan; PY Lau (Journal of Orthopaedic Surgery, 2004)
The superior dislocation of the patella with interlocking osteophytes is a rare condition. A review of the English literature revealed only 12 reported cases. The purpose of reviewing these case reports is to highlight the unusual presentation and the injury mechanism in 2 of our patients, and to present our treatment algorithm. Closed reduction with manipulation of the patella, with or without anaesthesia, was performed without difficulty. We recommend an intermediate step of trying a regional nerve block before proceeding to general anaesthesia. Our patients had full range-of-motion after reduction and they were symptom-free after 3 years of follow-up. There were no recurrent dislocations in our patients.